Aplikasi Informasi Pariwisata Daerah Banyuwangi Berbasis Android Dengan Memanfaatkan Google Maps - Adiputra, Ricky Fajar; Palit, Henry Novianus; Setiawan, Alexander (Jurnal Infra, 2016)
Banyuwangi is the eastern most regency of the island of Java. The regencyâs geography is quite diverse, from lowlands to mountains. Banyuwangi also has two nature reserves, which are very large and beautiful for visitors to see particularly marine nature. Tourism in Banyuwangi is also growing rapidly, ranging from city tours, marine tours, culinary tours, and other attractions. These attract many interests from tourists to visit Banyuwangi to see and enjoy tourism in Banyuwangi. However, the information about Banyuwangi tourism is quite difficult to obtain in a complete form and require a lot of time to collect from various sources. Relying on mobile devices that can be carried anywhere and easy internet access, an application for providing information to guide tourism in Banyuwangi was proposed.In this study, an Android-based tourism information application for Banyuwangi was developed. The application has many features that can help users, particularly information on places of interest, hotels, public transport, culinary, souvenir, and weather.Testing results show that the application can display local maps, routes, sorted list of places of interest by distance or travel time, weather forecast, and also provide an overview of Banyuwangi tourism through photographs and video clips. Using this application, the user can easily access tourism information in Banyuwangi.